Encapsulating bacteria in reactive magnesia cement for self-healing concrete - Tan, Ashley Ching Yee (Nanyang Technological University, 2021)
Cracks in concrete are inevitable and introduce problems that cause stress loss and affects the structural integrity of the structure. Manual repairing methods are costly and negatively impact the already burdened environment which emphasises the need for cheaper and sustainable methods. An increasingly popular alternative is the study of self-healing through microbial self-healing agents. The highly alkali concrete poses as a challenge to the survival of the bacteria when directly added, thus there is a need for encapsulation to protect it. Therefore, this paper investigates the feasibility of using Reactive Magnesia Cement (RMC), that has undergone accelerated carbonation, as the encapsulation material to protect the bacteria (Bacillus Cohnii) to achieve self-healing and concurrently, the mechanical properties of the matrix are not compromised. Crack width measurements and compressive strength tests were conducted to establish the feasibility, while SEM, XRD and calorimetry tests were conducted to shed light on the microstructure and morphology of the capsule and healing products. The gradient density characteristic of the capsule, of its outer surface being covered in hydrated magnesium carbonates (HMCs) with its core region of porous brucite identified from SEM and XRD tests, explained the reason for the compressive strength being unaffected by the capsule addition. The results from addition of the proposed MgO capsule and nutrients of yeast extract and calcium lactate into the PC matrix reported complete crack healing and an 8% increase in strength explained by the pre-reaction of bacteria on the surface of the capsule with the nutrients.